CONVENTIONS AND INVENTIONS OF THE DETECTIVE STORY FORMULA IN JONATHAN STROUD’S THE SCREAMING STAIRCASE - Baiq Jasnieta Anjani Putri; Iqbal Farhandika (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
Detective fiction is a formulaic genre that combines familiar narrative structures with the creative freedom of invention. According to John G. Cawelti, the detective story follows a recognizable pattern involving the introduction of a detective, the emergence of a mystery or crime, a logical investigative process, the announcement and explanation of the solution, and a conclusive resolution. This study analyzes Lockwood & Co.: The Screaming Staircase by Jonathan Stroud through the lens of Cawelti’s detective story formula to explore how conventional elements are maintained and what narrative inventions are introduced. The novel incorporates key conventions of the detective formula, such as a central mystery, investigation, and rational resolution. However, it also presents significant inventions, including supernatural disturbances as the central crime, teenage protagonists as investigators, and a fusion of detective and horror genres. Using a descriptive qualitative method, the analysis demonstrates that Stroud retains the structural core of the detective narrative while modifying its elements to suit a contemporary young adult and supernatural context. These findings highlight the flexibility of the detective story formula and its potential for transformation without losing narrative coherence.